2003
DOI: 10.1080/09540120310001595159
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related knowledge and adherence to HAART

Abstract: Near perfect adherence is considered essential for patients on HAART, yet adherence to medical recommendations is rarely so high. Supportive services and reminder tools may help individuals to become adherent, yet it is difficult to determine who may need such interventions. In this study, based on data from the NYSDOH/AIDS Institute Treatment Adherence Demonstration Program, we look at the association between HIV-related knowledge and adherence, hypothesizing that a better understanding of HIV and its treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 21 publications
1
37
0
2
Order By: Relevance
“…Psychological and social factors, and beliefs about and experience of ART have all been shown in other studies to be important in patient adherence to therapy [20,[23][24][25]. Strategies to improve adherence including directly observed therapy, pharmacist-assisted interventions, treatment advice clinics, treatment of mental illness, cognitive behavioural and educational interventions to improve patient knowledge around HIV and frequent home visits have been implemented with varying success [26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological and social factors, and beliefs about and experience of ART have all been shown in other studies to be important in patient adherence to therapy [20,[23][24][25]. Strategies to improve adherence including directly observed therapy, pharmacist-assisted interventions, treatment advice clinics, treatment of mental illness, cognitive behavioural and educational interventions to improve patient knowledge around HIV and frequent home visits have been implemented with varying success [26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A larger study conducted in recipients of Ryan White care in Miami found similar rates of (35%) individuals with less than high school education and would suggest that absence of high school education in HIV infected individuals may not be limited to Hispanic patients [16]. Related findings from other studies have found an association between lower literacy and lower HIV treatment adherence and knowledge in HIV infected patients [17][18][19] including knowledge of relevant disease parameters [20,21]. These findings along with those of the present study imply that low literacy, a commons equelae of limited or poor quality education, is a barrier to adequate HIV knowledge.…”
Section: Discussionmentioning
confidence: 81%
“…Our study results also show similar positive significant association of greater than 95% of adherence outcomes to HAART in ICG patients (67.5%, p<0.001) after having received EIs on adherence counseling in comparison with SCG. [25][26][27].…”
Section: Discussionmentioning
confidence: 99%